LANGSTON HUGHES AND HIS POETRY - Roza Eshbaeva Rustam qizi; Khamitov Eldor Erkinovich (TADQIQOTLAR.UZ, 2024)
The article offers a comprehensive overview of Langston Hughes's life and career, tracing his journey from his humble beginnings in Joplin, Missouri, to his pivotal role in the Harlem Renaissance and beyond. Born into a fractured family, Hughes found solace in literature and poetry, which became the cornerstone of his identity and artistic expression. Through his seminal works like "The Negro Speaks of Rivers" and "The Weary Blues," Hughes captured the essence of African American experiences, earning him acclaim as the "Poet Laureate of Harlem." His exploration of jazz poetry, infused with rhythms and themes reflective of Black life, further solidified his status as a literary pioneer. Despite facing racial barriers at Columbia University, Hughes thrived within the vibrant cultural milieu of Harlem, forging connections and contributing to the burgeoning artistic movement. His dedication to portraying the struggles and triumphs of ordinary Black Americans, as evidenced in works like "Fine Clothes to the Jew," underscored his commitment to authenticity and representation. Through his bold declarations in essays such as "The Negro Artist and the Racial Mountain," Hughes advocated for artistic autonomy and self- affirmation within the Black community, leaving an indelible mark on American literature and cultural discourse.